CLAYS FROM THE PARIQUERA-AÇU FORMATION: GEOLOGY, GEOCHEMISTRY AND ITS APPLICATION AS CERAMIC RAW MATERIAL - Christofoletti, Sérgio Ricardo; Motta, José Francisco Marciano; Meneghel, Eduardo Camargo [UNESP] (My University, 2022)
The present work had as main focus to study the lake facies of the Pariquera-Açu Formation as a source of raw material for the ceramic tile industry, especially in the production of porcelain stoneware tiles. To achieve the proposed objectives, the geological study was carried out through the mapping and recognition of the present lithologies, where samples were collected and later sent to laboratories for the analysis of X-ray diffraction, X-ray fluorescence, cation exchange capacity and characterization technology for use as ceramic tiles. According to the results obtained, the lithological set of these facies is essentially represented by clay and plastic rocks, presenting an essentially silica aluminous composition with a high content of SiO2 and Al2O3 oxides, where the minerals quartz, microcline and calcite and the kaolinite and mineral minerals predominate. Illita. According to the technological results, most of the samples were classified in Groups BIII (porous) and BIIb (semi-porous). The low results of dry MRF and melting elements of the studied samples, limit its use as a single raw material in the production of ceramic coating by dry and wet by way, however some samples showed high dry density (DA) and burning color clear, which allows it to be used in the composition of masses for the manufacture of glazed porcelain tiles by the wet process.
ARGILAS DA FORMAÇÃO PARIQUERA-AÇU: GEOLOGIA, GEOQUÍMICA E SUA APLICAÇÃO COMO MATÉRIA-PRIMA CERÂMICA
Keywords: Ceramic raw material; Lithogeochemistry; Pariquera-Açu Formation; Porcelain tiles; Ribeira Valley